1985
DOI: 10.1111/j.1745-4549.1985.tb00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Change in Physical and Quality Parameters of Fluid Foods During Continuous Flow Heating. Application to Liquid Whole Egg

Abstract: A fluid in continuous flow heating approaches maximum thermal treatment as the viscosity profile becomes plug flow. This effect is examined for physical and quality changes in tubular heating of fluid foods. Arrhenius mathematical forms of constituent change are incorporated into the thermal profile models for the general case. Application to soluble protein loss (SPL) and viscosity change in liquid whole egg (LWE) are used as examples. Time and temperature schedules are suggested for pasteurization of LWE at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…(1)] was also applied to shear stress shear rate data of LWE [25] Hamid Samimi et al, [13] and Hamid-Samimi and Swartzel. [14] They reported that whole egg behaves as a Newtonian fluid below 60°C and pseudoplastic at temperatures above 60°C. Tung et al [26] also observed that egg white is slightly pseudoplastic at its respective pasteurization temperature.…”
Section: Rheological Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…(1)] was also applied to shear stress shear rate data of LWE [25] Hamid Samimi et al, [13] and Hamid-Samimi and Swartzel. [14] They reported that whole egg behaves as a Newtonian fluid below 60°C and pseudoplastic at temperatures above 60°C. Tung et al [26] also observed that egg white is slightly pseudoplastic at its respective pasteurization temperature.…”
Section: Rheological Behaviormentioning
confidence: 99%
“…Although several researchers [12,13,14,15,16,17,18,19] investigated the rheological properties of liquid egg products, there are different conclusions reported about the rheological behavior of LEPs. The results of these studies showed Newtonian, as well as time-dependent non-Newtonian flow behavior of egg.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid foods are subjected to different temperatures during processing, storage, transportation, marketing, and consumption. For this reason, the rheological properties are studied as a function of temperature (Hamid-Samimi and Swartzel 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Liquid egg products (LEP) are valuable due to their high protein content, low cost, and being used as ingredients in a prepared meal in order to provide texture, flavor, structure, moisture (Hamid-Samimi & Swartzel, 1985;Punidadas & McKellar, 1999).…”
Section: Introductionmentioning
confidence: 99%